A by product blended diet to reduce enteric methane emissions from sheep in Argentina - Gualdrón Duarte, Laura (2025)
While livestock production is a significant source of greenhouse gas emissions, it remains vital for fulfilling the growing global demand for animal protein. Including by-products in ruminant diets can enhance food circularity and reduce competition for human food, while also increasing the likelihood of reducing methane (CH4) emissions. This study aimed to evaluate the impact of fully replacing corn grain and urea in the control diet with local by-products, specifically corn distillers’ grains combined with either barley brewed grains or with wheat middlings, on enteric CH4 emissions and performance of sheep. Diets were balanced to be isoproteic and isoenergetic with 2.6 Mcal ME/kg of dry matter (DM) and 160 g crude protein/kg DM, respectively. Corn silage is the only source of forage in the diet, and the forage-to-concentrate ratio was maintained to 60:40 on a DM basis. Twelve Highlander female sheep of 35.9 ± 3.12 kg initial body weight (BW, mean ± standard deviation), were used in a Completely Randomized Block design, with four sheep per treatment and two measurement periods under the same treatment. Experiment lasted 60 d, 30 d acclimatization and 30 d measurements. Dry matter intake (DMI) was restricted to 2.5% of BW. Enteric CH4 emissions of individual sheep were quantified in respiration chambers over a 48 h period. Dietary treatments did not have a significant effect either on DMI or BW gain. The diet containing barley brewed grains significantly reduced total daily CH4 production by 22.3%, CH4 emissions per kg of DMI by 34% and energy loss as CH4 by 38% compared to the control diet. In conclusion, the agro-industrial by-products combinations evaluated in this study effectively replaced corn grain and urea without compromising feed intake or animal performance. Additionally, the diet containing barley brewed grains significantly reduced CH4 yield, and energy loss compared to the control diet.